2010
DOI: 10.1155/2010/319138
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Surface Ozone Pollution in the Central Gulf Coast Region Using WRF/Chem Model: Sensitivity to PBL and Land Surface Physics

Abstract: The fully coupled WRF/Chem (Weather Research and Forecasting/Chemistry) model is used to simulate air quality in the Mississippi Gulf coastal region at a high resolution (4 km) for a moderately severe summer ozone episode between 18 CST 7 and 18 CST 10 June 2006. The model sensitivity is studied for meteorological and gaseous criteria pollutants (O3, NO2) using three Planetary Boundary Layer (PBL) and four land surface model (LSM) schemes and comparison of model results with monitoring station observations. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 50 publications
(70 reference statements)
1
17
0
1
Order By: Relevance
“…The simulations overestimate the nighttime winds (Figures b, f, j, and n) but present similar wind biases for coastal regions including the Houston area as was found in previous studies such as those by Misenis et al (), Cheng and Steenburgh (), Roux et al (), Yerramilli et al (), Ngan et al (), and Cuchiara et al (). In the model, the arrival times of the sea and bay breezes are about 2 hr later when compared with the observations (Figure ).…”
Section: Case Studysupporting
confidence: 87%
“…The simulations overestimate the nighttime winds (Figures b, f, j, and n) but present similar wind biases for coastal regions including the Houston area as was found in previous studies such as those by Misenis et al (), Cheng and Steenburgh (), Roux et al (), Yerramilli et al (), Ngan et al (), and Cuchiara et al (). In the model, the arrival times of the sea and bay breezes are about 2 hr later when compared with the observations (Figure ).…”
Section: Case Studysupporting
confidence: 87%
“…In the 1‐D REAM, vertical mixing is driven by the WRF‐generated parameters such as turbulent diffusivity, which is computed by BL and land‐surface schemes in WRF. A number of studies compared the performance of these WRF schemes in terms of meteorological parameters such as temperature and humidity [ Gilliam and Pleim , ; Hu et al , ; Shin and Hong , ; Xie et al , ], but few evaluated their influence on chemical tracers [ Yerramilli et al , ; Pleim , ]. To test how the choices of BL and land‐surface schemes impact vertical mixing in the 1‐D REAM, we choose three BL schemes (MYJ, YSU, and ACM2) and two land‐surface schemes (Noah and RUC) in WRF and evaluate their performance with the DISCOVER‐AQ 2011 observations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study (Žabkar et al, 2013) reported that the model physics parameterization schemes of PBL, LW, SW, surface layer (SL) and land-surface model (LSM) were of great importance for simulation results. Yerramilli et al (2010) advocated that the simulation using the Noah LSM scheme often showed the best consistency with observation. This conclusion had been proved in our experimental study.…”
Section: Introductionmentioning
confidence: 95%